Resistive-type hydrogen gas sensor based on TiO2: A review. (8th November 2018) - Li, Zhong; Yao, ZhengJun; Haidry, Azhar Ali; Plecenik, Tomas; Xie, LiJuan; Sun, LinChao; Fatima, Qawareer
Abstract: Owing to its high energy density and environmentally friendly nature, hydrogen has already been regarded as the ultimate energy of the 21st century and gained significant attention from the worldwide researchers. Meanwhile, there are increasing concerns about its safe use, storage and transport as, despite being colorless and odorless, after certain concentration level it becomes flammable and explosive in air. Therefore, it is imperative to develop H2 sensors for real-time monitoring of the H2 leakage for an early warning. This paper firstly introduces the general hydrogen gas sensing mechanism of TiO2 -based hydrogen sensors. Then we summarize and comment on the current hydrogen gas sensor based on various TiO2 materials, which include pristine TiO2, metal-assisted TiO2, organic-TiO2 composites, carbon-TiO2 composites, MOX-TiO2 composites and novel sensor concept with effective top-bottom electrode configuration. Finally, we briefly discuss the obstacles that TiO2 -based H2 sensors have to overcome in the progress of the systematically practical application, possible solutions, and future research perspectives that can be focused in this area. Highlights: General hydrogen gas sensing mechanism based on TiO2 were introduced. Hydrogen gas sensor based on various TiO2 materials were summarized and commented. The obstacles that TiO2 based hydrogen sensor have to overcome were stated briefly. Future research perspectives of the hydrogen gas sensor are proposed and discussed.